Princess [compact disc, unabridged] - Patterson, James, 1947-; Jones, Rees, 1983- (Patterson, James, 1947- Private novels., 2018)
Princess Caroline, third in line to the British throne, needs Jack Morgan's skills. A close friend of the princess has gone missing, and she needs to be found before the media become aware of it. Morgan knows there is more to the case than he is being told. But what is the princess hiding?